New Algorithms for Balancing Energy Consumption and Performance in Computational Clusters - Tran, Xuan Thi; Do, Tien Van; Vu, Binh Thai (Computing and Informatics, 2017)
In this paper, we propose new real-time measurement-based scheduling algorithms to achieve a trade-off between the energy efficiency and the performance capability of computational clusters. An investigation is performed using a specific scenario of computing clusters with realistic parameters. Numerical results show that a trade-off between the performance and the energy efficiency can be controlled by the proposed algorithms.